2009
DOI: 10.1016/j.jtcvs.2009.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Solitary fibrous tumors of the pleura: Results of surgical treatment and long-term prognosis

Abstract: Objective We sought to define the long-term outcome of surgically treated solitary fibrous tumors of the pleura. Methods We performed a retrospective review from December 1972 through December 2002. Results There were 84 patients (39 men and 45 women) with a median age of 57 years (range, 34–83 years). Forty-six patients were symptomatic. Surgical resection included pulmonary wedge excision in 62 patients, lobectomy in 4 patients, segmentectomy in 2 patients, chest wall resection in 3 patients, isolated pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
113
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(131 citation statements)
references
References 16 publications
6
113
2
8
Order By: Relevance
“…10 Nonetheless, in spite of a higher proportion of patients exhibiting tumor characteristics associated with malignant behavior, we only observed a recurrence rate of 8%, compared with a 14% recurrence rate reported in the American population 10 and a 10% to 15% recurrence rate reported in contemporary surgical series. [2][3][4][5][6] We have also demonstrated that the proposed score performed signifi cantly better in this validation population compared with previously published criteria to determine malignant behavior, specifi cally, the criteria by England et al 8 and the classifi cation by de Perrot et al 9 Additionally, the scoring system remained valid upon classifying patients according to their risk of SFTP recurrence when using a cutoff of 3 points. In patients classifi ed at low risk ( , 3 points), we observed very low recurrence rates of 1.3%, 1.3%, and 3.5% at 5, 10, and 15 years, respectively, compared with recurrence rates of 13.5%, 17.5%, and 27.9% in patients classifi ed at high risk ( Ն 3 points).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…10 Nonetheless, in spite of a higher proportion of patients exhibiting tumor characteristics associated with malignant behavior, we only observed a recurrence rate of 8%, compared with a 14% recurrence rate reported in the American population 10 and a 10% to 15% recurrence rate reported in contemporary surgical series. [2][3][4][5][6] We have also demonstrated that the proposed score performed signifi cantly better in this validation population compared with previously published criteria to determine malignant behavior, specifi cally, the criteria by England et al 8 and the classifi cation by de Perrot et al 9 Additionally, the scoring system remained valid upon classifying patients according to their risk of SFTP recurrence when using a cutoff of 3 points. In patients classifi ed at low risk ( , 3 points), we observed very low recurrence rates of 1.3%, 1.3%, and 3.5% at 5, 10, and 15 years, respectively, compared with recurrence rates of 13.5%, 17.5%, and 27.9% in patients classifi ed at high risk ( Ն 3 points).…”
Section: Discussionmentioning
confidence: 77%
“…Th e infrequent presentation of SFTPs has limited their study to mostly case reports and single-institution case series. [2][3][4][5][6][7] Since 1989, 8 factors associated with SFTP malignant behavior have been recognized. However, surgical series have used diff erent criteria to classify tumors as "malignant."…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations